2006
DOI: 10.4269/ajtmh.2006.74.884
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Home-Based Chlorination and Safe Water Storage in Reducing Diarrhea Among Hiv-Affected Households in Rural Uganda

Abstract: Safe water systems (SWSs) have been shown to reduce diarrhea and death. We examined the cost-effectiveness of SWS for HIV-affected households using health outcomes and costs from a randomized controlled trial in Tororo, Uganda. SWS was part of a home-based health care package that included rapid diarrhea diagnosis and treatment of 196 households with relatively good water and sanitation coverage. SWS use averted 37 diarrhea episodes and 310 diarrhea-days, representing 0.155 disability-adjusted life year (DALY)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…An evaluation of use of BCP components over time in both the Ethiopian and Ugandan programs is warranted and could help guide programming. In addition, an assessment of the costs and benefits of a program of free resupply of BCP commodities would be useful for guiding policy, [32], [33] particularly in view of evidence that integration of free health interventions into health services can serve as an incentive to increase use of services [34].…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of use of BCP components over time in both the Ethiopian and Ugandan programs is warranted and could help guide programming. In addition, an assessment of the costs and benefits of a program of free resupply of BCP commodities would be useful for guiding policy, [32], [33] particularly in view of evidence that integration of free health interventions into health services can serve as an incentive to increase use of services [34].…”
Section: Discussionmentioning
confidence: 99%
“…Household-based disinfection was also found to be among the most cost-beneficial of the water and sanitation interventions (Hutton & Haller 2004). A recent CEA assessed the cost-effectiveness of home-based chlorination among HIV-affected households in Uganda (Shrestha et al 2006). Our study builds on previous research by (i) using more broad-based estimates of cost and effectiveness of the interventions, (ii) comparing conventional non-reticulated source-and four householdbased interventions to improve water quality, and (iii) employing the generalized CEA methodology developed by WHO-CHOICE to permit a comparison of each of these interventions in the context of other Millennium Development Goal (MDG) health initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…One study assessing the potential cost-effectiveness of a population-level water supply and sanitation intervention demonstrated that oral rehydration solution plus hygiene education would cost US$ 2.93 per episode of diarrhea averted [72]. Another study, on a home-based chlorination and safe water storage intervention to reduce diarrhea among people living with HIV in rural Uganda, estimated a cost of US$ 5.21 per episode of diarrhea averted [73]. A study in Burkina Faso analyzed the cost-effectiveness of a large-scale urban hygiene promotion program, finding an incremental cost of US$ 51.30 per case of child diarrhea prevented from the societal perspective [74].…”
Section: Discussionmentioning
confidence: 99%